Modelling of paste ram extrusion subject to liquid phase migration and wall friction. (23rd November 2017) - Patel, M.J.; Blackburn, S.; Wilson, D.I.
Highlights: Effects of wall friction on LPM during 2-D axisymmetric ram extrusion are modelled. Effects of friction factor, die shape & ram displacement on flow & LPM are coupled. Using conical entry dies can promote or reduce LPM depending on the friction factor. Yield stress, permeability and wall slip models are critical to predictive accuracy. Abstract: Extrusion of solid-liquid particulate pastes is a well-established process in industry for continuously forming products of defined cross-sectional shape. At low extrusion velocities, the solids and liquid phases can separate due to drainage of liquid through the interparticle pores, termed liquid phase migration (LPM). The effect of wall friction, die shape and extrusion speed on LPM in a cylindrically axisymmetric ram extruder is investigated using a two-dimensional finite element model of paste extrusion based on soil mechanics principles (modified Cam-Clay). This extends the smooth walled model reported by Patel et al. (2007) to incorporate a simplified Tresca wall friction condition. Three die entry angles (90°, 60° and 45°) and two extrusion speeds are considered. The extrusion pressure is predicted to increase with the Tresca friction factor and the extent of LPM is predicted to increase with decreasing ram speed (both as expected). The effects of wall friction on LPM are shown to be dictated by the die shape and ram displacement: there are few general rules relating extruder design and operating conditions to extent of LPM, so that finite element-based simulation is likely to be needed to predict the onset of LPM accurately.